Students’ obstacles in solving algebra form problems viewed from mathematical problem-solving ability - Wahyuni, Reni; Suwanto, Fevi Rahmawati; Sthephani, Aulia; Ahyan, Shahibul (IKIP Siliwangi and I-MES, 2025)
Mathematical problem-solving ability is the most effective cognitive instrument in learning mathematics, and enhancing students' mathematical problem-solving ability is the primary objective of education. However, to reach the most effective level of mathematical problem-solving ability, we need to comprehend the reasons behind students' challenges while learning. This research investigates the learning obstacles of the students based on their mathematical problem-solving ability, particularly in algebraic form material. The method used in this research employed qualitative study with a series of Didactical Design Research (DDR) projects to learn the obstacles to the student's mathematical problem-solving ability. Seventy-six eighth-grade students from a public junior high school in Kampar region were given a test to assess their ability to solve mathematical problems. Various research instruments are used, including tests of mathematical problem-solving ability, interview guidelines, and interviews by audio recordings. The data were analyzed using a qualitative approach to determine students' learning obstacles. The findings highlight ontogenic, epistemological, and didactical obstacles students face while understanding the problem, particularly the concept of algebraic form, interpreting the word to the mathematical concept of algebraic form, and designing the algebraic forms.